Pomegranate extract in polyphosphate-fluoride mouthwash reduces enamel demineralization - Vieira, Ana Paula Miranda [UNESP]; Danelon, Marcelle [UNESP]; Fernandes, Gabriela Lopes [UNESP]; Berretta, Andresa Aparecida; Buszinski, Andrei Felipe Moreira; dos Santos, Lucinéia [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Barbosa, Debora Barros [UNESP] (Springer Nature, 2024)
Objectives: To evaluate the anti-demineralizing effect of a mouthwash comprising pomegranate peel extract (PPE 3%), sodium trimetaphosphate (TMP 0.3%), and fluoride (F 225 ppm) in an in situ study, and to assess its irritation potential in an ex vivo study. Methods: This double-blind crossover study was conducted in four phases with 7 days each. Twelve volunteers used palatal appliances containing enamel blocks, which were subjected to cariogenic challenges. The ETF formulation (PPE + TMP + F, pH 7.0), TF formulation (TMP + F, pH 7.0), deionized water (W, pH 7.0), and essential oil commercial mouthwash (CM, 220 ppm F, pH 4.3) were dropped onto the enamel twice daily. The percentage of surface hardness loss, integrated loss of subsurface hardness, calcium, phosphorus, and fluoride in enamel and biofilms were determined. In addition, alkali-soluble extracellular polysaccharide concentrations were analyzed in the biofilms. The irritation potential was evaluated using the hen’s egg chorioallantoic membrane test through the vascular effect produced during 300-s of exposure. Results: ETF was the most efficacious in preventing demineralization. It also showed the highest concentrations of calcium and phosphorus in the enamel and in the biofilm, as well as the lowest amount of extracellular polysaccharides in the biofilm. In the eggs, ETF produced light reddening, whereas CM led to hyperemia and hemorrhage. Conclusions: The addition of PPE to formulations containing TMP and F increased its anti-demineralizing property, and this formulation presented a lower irritation potential than the CM. Clinical relevance: ETF can be a promising alternative alcohol-free mouthwash in patients at high risk of caries.
Keywords: Chick embryo; Dental caries; Fluorides; Mouthwashes; Phosphates; Pomegranate